ETHNOPHARMACOLOGICAL IMPORTANCE OF MORINDA CITRIFOLIA L. - Padmavathy, S.; Jeyachandran, R.; Cindrella, L. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Morinda citrifolia L. (commonly known as Noni) has been used in folk remedies over the years and has a broad range of therapeutic effects, including antibacterial, antiviral, antifungal, antitumor, analgesic, hypotensive, anti-inflammatory, and immune enhancing effects. The effect of oral administration of the bioactive principles isolated from Morinda citrifolia. L was studied in streptozotocin induced diabetic nephropathy rats to assess the anti-diabetic nephropathy activity in terms of glucose, protein, urea, uric acid, creatinine in serum, potassium, sodium, alkaline phosphatase and urinary craetinine. Streptozotocin induced animals showed high level of protein compared to control group. The increased serum protein level is due to increased renal failure with progressive atrophy of the nephrons. Treatment of diabetic nephropathy rats with Morinda citrifolia fruit extract has been found to decrease the damage of kidney and has restored the level of glucose, protein, urea, uric acid, creatinine, potassium, sodium and kidney alkaline phosphatase to that of normal level. Noni is rich in proxeronine, which combines with enzymes in the body to form an essential substance known as xeronine. It activates the immune system at cellular level thereby repairing and protecting kidney from damage. The extract of noni is found to possess nephroprotective effects as revealed by the histopathological studies. The fruit extract of the plant has anti-diabetic nephropathy effects, and possesses both high antioxidant properties and immunomodulatory properties. Morinda is believed to fortify and maintain cell structures. This can be accomplished by acting as an adaptogen that can aid ”sick” cells in repairing themselves.